Transparent polyurethane hot melt adhesive and preparation method thereof

By using transparent polyurethane hot melt adhesive, combined with waste PET sheets and poly(carbonate-ether) glycol and other raw materials, the problem of PET waste not being recycled in high value and polyurethane hot melt adhesive being overly dependent on petrochemical resources is solved, and the problem of PET waste being unable to be recycled and utilized is achieved. Efficient PET recycling and sustainable polyurethane hot melt adhesive production.

CN119463780APending Publication Date: 2025-02-18CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411679637.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, PET waste cannot be recycled at a high value, and traditional polyurethane hot melt adhesives rely too much on petrochemical resources, resulting in environmental pollution and unsustainable development.

Method used

Transparent polyurethane hot melt adhesive is used, and its raw materials include waste PET sheets, poly(carbonate-ether) diols, etc., through specific component ratios and preparation methods, PET waste can be maximized and utilization can be reduced. rely.

Benefits of technology

It realizes the high-value recycling of PET waste, reduces consumption of petrochemical resources, improves the transparency, adhesion and mechanical properties of transparent polyurethane hot melt adhesives, and provides a sustainable development solution for the plastic recycling industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463780A_ABST
    Figure CN119463780A_ABST
Patent Text Reader

Abstract

The invention discloses a transparent polyurethane hot melt adhesive and a preparation method thereof, relates to the technical field of polyurethane hot melt adhesives, and solves the problems that PET (Polyethylene Terephthalate) waste cannot be recycled in a high-valued manner and the traditional polyurethane hot melt adhesive excessively depends on petrochemical resources in the prior art. The transparent polyurethane hot melt adhesive prepared by the preparation method disclosed by the invention is prepared from the following components in parts by mass through reaction: 420 to 510 parts of waste PET (Polyethylene Terephthalate) sheets, 35 to 48 parts of sulfur-containing dihydric alcohol, 0.15 to 0.30 part of an antioxidant, 0.18 to 0.47 part of a catalyst I, 180 to 240 parts of poly (carbonate-ether) dihydric alcohol, 0.05 to 0.12 part of a catalyst II and 115 to 142 parts of diisocyanate. The transparent polyurethane hot melt adhesive has high transparency and excellent glass adhesion, high-valued recovery of PET waste can be realized, excessive dependence on petrochemical resources is reduced, and a new thought is provided for development of sustainable materials in the plastic recovery industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane hot melt adhesives, and in particular to a transparent polyurethane hot melt adhesive and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) is one of the most widely used synthetic resins today, and is used in beverage bottles, food packaging, textiles, electronic equipment housings and other fields. Due to its excellent mechanical properties, heat resistance and chemical stability, PET occupies an important position in industrial production. However, with the large-scale production and use of PET, the resulting environmental problems have become more severe. As a non-biodegradable plastic material, the accumulation and treatment of PET waste has put tremendous pressure on the environment. Data show that in 2018, the global annual production of PET reached 79.68 million tons, and its waste reached 10 million tons. However, data in 2023 showed that its recycling rate was only 6.5 million tons, accounting for 32%. Traditional methods for treating PET waste include landfill, incineration and physical degradation and recycling technology, but due to the special aromatic ring structure of PET, it is difficult to degrade in nature. PET waste takes hundreds of years to decompose in nature, which means that they will exist in the ecological environment for a long time, affecting the quality of soil, water and air. At the same time, the incineration of PET plastics will release toxic gases, further aggravating air pollution and threatening human health. In addition, the use of physical degradation and recycling technology to treat PET waste cannot achieve high-value recycling of waste PET; even if the preparation of monomers through depolymerization to recycle PET waste is an efficient chemical recycling method, its complex post-processing will increase the recycling cost.

[0003] Polyurethane hot melt adhesive is an important adhesive with excellent bonding properties, low temperature resistance and shear resistance, which makes polyurethane hot melt adhesive have certain application potential in the recycling and reuse of PET. However, the synthesis of polyurethane hot melt adhesive is heavily dependent on petrochemical resources. It is usually prepared from petroleum-based polymer diols and diisocyanates. It also releases greenhouse gases, increases carbon emissions, and has a negative impact on the environment, causing it to face the dilemma of unsustainable development. Therefore, in order to solve the problem that PET waste cannot be recycled at a high value and the traditional polyurethane hot melt adhesive is overly dependent on petrochemical resources, the development of a new structure of PET-based polyurethane hot melt adhesive material has become a hot topic of current research, providing a greener and more efficient solution for the sustainable development of the plastic recycling industry. Summary of the invention

[0004] In order to solve the problem that PET waste cannot be recycled at a high value in the prior art and that traditional polyurethane hot melt adhesives are overly dependent on petrochemical resources, the present invention proposes a transparent polyurethane hot melt adhesive and a preparation method thereof. The technical solution of the present invention is as follows:

[0005] A transparent polyurethane hot melt adhesive is prepared by reacting the following components in parts by weight:

[0006] 420-510 parts of waste PET flakes, 35-48 parts of sulfur-containing diols, 0.15-0.30 parts of antioxidants, 0.18-0.47 parts of catalysts I, 180-240 parts of poly(carbonate-ether) diols, 0.05-0.12 parts of catalysts II, and 115-142 parts of diisocyanates;

[0007] The catalyst I is one or a combination of at least two of tetrabutyl titanate, tetraisopropyl titanate, diethyl zinc, zinc octoate, zinc acetate, manganese acetate, manganese phosphate, zinc phosphate, calcium phosphate, zinc oxide and zinc chloride;

[0008] The catalyst II is one or a combination of at least two of dibutyltin dilaurate, stannous octoate and bismuth neodecanoate;

[0009] The sulfur-containing diol is one or a combination of at least two of 3,7-dithia-1,9-nonanediol, 3,5-dithia-1,7-heptanediol, 2,2′-thiodiethanol, 3,6-dithia-1,8-octanediol and 1,4-dithia-2,5-diol;

[0010] The antioxidant is one or a combination of at least two of triethyl phosphite, pentaerythritol bisphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, dioctadecylpentaerythritol diphosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine;

[0011] The poly(carbonate-ether) diol is prepared according to the preparation method disclosed in Chinese patent document 201110231493.6;

[0012] The diisocyanate is one or a combination of at least two of isophorone diisocyanate, 1,6-hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,4-cyclohexane diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexane dimethyl diisocyanate and norbornane diisocyanate;

[0013] The number average molecular weight Mn of the poly(carbonate-ether) diol is 3300-6000, and the carbonate unit content CU is 30%-36%.

[0014] A method for preparing the above transparent polyurethane hot melt adhesive comprises the following steps:

[0015] S1: Under nitrogen protection, waste PET sheets, sulfur-containing diol, catalyst I and antioxidant are sequentially put into a reactor for heating treatment, and stirred to react after reaching the temperature to obtain a first intermediate;

[0016] S2: adding the first intermediate, poly(carbonate-ether) diol, catalyst II and diisocyanate into the reaction screw, setting the heating temperature of each stage of the reaction screw, and after the heating is completed, cutting the reactants into strips underwater to obtain transparent polyurethane hot melt adhesive particles;

[0017] Further, the temperature of the reactor in S1 is raised to 120-180° C.;

[0018] Furthermore, the reaction time in S1 is 0.5 to 2.5 h;

[0019] Further, the heating temperatures in each stage of S2 are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C in sequence;

[0020] Furthermore, the heating temperature retention time in each stage of S2 is 3 to 5 minutes.

[0021] Compared with the prior art, the present invention solves the problem that the prior art PET waste cannot be recycled at a high value and the traditional polyurethane hot melt adhesive is overly dependent on petrochemical resources. The specific beneficial effects are:

[0022] 1. High-value recycling of PET waste: The raw materials for preparing the transparent polyurethane hot melt adhesive of the present invention include waste PET sheets, poly(carbonate-ether) diols, etc., wherein the components of the poly(carbonate-ether) diols are PET alcoholysis products, which maximizes the recycling of PET waste and reduces the serious consumption of petrochemical resources. At the same time, the rigidity, polarity and transparency of PET are utilized to significantly improve the transparency, adhesion and mechanical properties of the transparent polyurethane hot melt adhesive, which not only effectively solves the problem of PET waste treatment, realizes the high-value utilization of plastic resources, but also provides new ideas for the sustainable development of the plastic recycling industry.

[0023] 2. Reduce excessive reliance on petrochemical resources: The preparation process of traditional polyurethane hot melt adhesives is usually overly dependent on petrochemical raw materials, such as petroleum-based isocyanates, polyols, etc. The transparent polyurethane hot melt adhesive provided by the present invention uses waste PET sheets as the main raw material, and the component of the poly(carbonate-ether) diol used is the alcoholysis product of PET, which effectively reduces excessive reliance on petrochemical resources; this raw material substitution strategy not only helps to reduce the consumption of non-renewable resources, but also can alleviate the impact of PET waste on the ecological environment to a certain extent, and also effectively reduces the production input cost of transparent polyurethane hot melt adhesive, which has positive significance for improving the stability and sustainability of the industrial chain.

[0024] 3. High transparency: The light transmittance of the transparent polyurethane hot melt adhesive prepared by the present invention is as high as 93.5-98.3%, which is 50.8-74.3% higher than similar products; the haze is 0.15-0.26%, which is 1.7-4.6% lower than similar products. This is because the used raw material waste PET sheet itself has excellent transparency, and the amorphous structure of poly (carbonate-ether) diol can maintain its good transparency by reducing the light scattering caused by crystallization. The use of the two effectively enhances the transparency of the transparent polyurethane hot melt adhesive. At the same time, the introduction of heteroatom sulfur into the transparent polyurethane hot melt adhesive enhances the regulation of heteroatom sulfur on the dual soft segment structure of waste PET sheet and poly (carbonate-ether) diol and optimizes the compatibility between the two, thereby reducing the haze and light scattering of the material, thereby enhancing the transparency.

[0025] 4. Excellent glass adhesion: The peel strength of the transparent polyurethane hot melt adhesive prepared by the present invention is 3.2-4.7 N / mm, which is 0.5-2.4 N / mm higher than similar products. This is due to the characteristics of polar groups (such as carboxyl, carbonate and ether groups) in the molecular structure of PET and poly (carbonate-ether) diols that can undergo physical adsorption and synergistic effects with the glass surface to enhance the adhesion of the transparent polyurethane hot melt adhesive; in addition, the presence of the amorphous structure of poly (carbonate-ether) diols and carbonate groups with high cohesive energy can enhance the tensile strength and elongation at break of the transparent polyurethane hot melt adhesive, further enhancing its adhesion to glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an infrared spectrum of the transparent polyurethane hot melt adhesive prepared in Example 1;

[0027] Figure 2 This is a photo of the transparent polyurethane hot melt adhesive particles prepared in Example 1;

[0028] Figure 3 This is a photo of the hot melt adhesive particles prepared in Comparative Example 1. DETAILED DESCRIPTION

[0029] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0030] The poly(carbonate-ether) diol used in the following examples is prepared according to the preparation method disclosed in patent document 201110231493.6, specifically the poly(carbonate-ether) diol corresponding to Example 8, Example 12, Example 15 and Example 17 in the specification of the patent document.

[0031] Example 1.

[0032] S1: Under nitrogen protection, 420 g of waste PET sheets, 35 g of 2,2′-dithioethanol, 0.18 g of tetrabutyl titanate and 0.15 g of triethyl phosphite were sequentially added into a reactor, and stirring was started after the temperature rose to 120° C. The reaction was continued for 2.5 h to obtain a first intermediate;

[0033] S2: The first intermediate, 180g of poly(carbonate-ether) diol (Mn=3300, CU=30.6%), 0.05g of dibutyltin dilaurate and 115g of isophorone diisocyanate are added to the reaction screw. The heating temperatures of the reaction screw in each stage are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively. The heating time for each stage is 3min. After the end, the product is stretched and pelletized underwater to obtain transparent polyurethane hot melt adhesive particles.

[0034] like Figure 1 Infrared spectrum of transparent polyurethane hot melt adhesive: 731.0cm -1 , 795.6cm -1 , 873.7cm -1 , 944.1cm -1 , 1017.4cm -1 , 1046.3cm -1 , 1104.2cm -1 , 1121.5cm -1 , 1170.7cm -1 , 1272.1cm -1 , 1378.1cm -1 , 1408.9cm -1 , 1455.2cm -1 , 1505.3cm -1 , 1580.6cm -1 , 1616.3cm -1 , 1721.4cm-1 , 1954.8cm -1 , 2957.6cm -1 ,3064.7cm -1 , 3434.1cm -1 As can be seen from the figure, 1721.4cm - The strong absorption peak at 1 corresponds to the stretching vibration of the carbonyl group (C=O), which is the key feature of polyurethane molecules; - The broad peak at 731.0 cm-1 indicates that there are significant hydrogen bonding interactions within or between the molecules of the transparent polyurethane hot melt adhesive, which further proves that it has a soft segment structure inside. - 1 and 1616.3cm - The peak at 1 reveals the presence of aromatic rings in isocyanate; at the same time, the peak at 1017.4-1121.5 cm - The peak at 1 represents the vibration of the COC bond, proving that the soft segment structure of the transparent polyurethane hot melt adhesive contains polyether groups. In summary, the transparent polyurethane hot melt adhesive has a typical polyurethane structure with microphase separation of soft segments and hard segments, which gives it excellent adhesion, flexibility and thermal stability. Figure 2 This is a photo of the transparent polyurethane hot melt adhesive particles prepared in this example. It can be seen from the figure that the polyurethane hot melt adhesive is transparent.

[0035] Example 2.

[0036] S1: Under nitrogen protection, 510 g of waste PET sheets, 48 ​​g of 3,7-dithia-1,9-nonanediol, 0.47 g of tetraisopropyl titanate and 0.30 g of pentaerythritol diphosphite were sequentially added into a reaction kettle, and stirring was started after the temperature was raised to 180° C. The reaction was carried out for 0.5 h to obtain a first intermediate;

[0037] S2: The first intermediate, 240 g of poly(carbonate-ether) diol (Mn=6000, CU=34.3%), 0.12 g of stannous octoate and 142 g of 4,4'-dicyclohexylmethane diisocyanate are added to the reaction screw. The heating temperatures of the reaction screw in each stage are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C, and 140°C, respectively. The heating time for each stage is 5 min. After the end, the product is stretched and pelletized underwater to obtain transparent polyurethane hot melt adhesive particles.

[0038] Example 3.

[0039] S1: Under nitrogen protection, 460 g of waste PET sheets, 37 g of 3,5-dithia-1,7-heptanediol, 0.23 g of diethyl zinc and 0.21 g of bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite were sequentially added into a reaction kettle, and stirring was started after the temperature rose to 140° C. The reaction was carried out for 1.5 h to obtain a first intermediate;

[0040] S2: The first intermediate, 200 g of poly(carbonate-ether) diol (Mn=3500, CU=54.8%), 0.08 g of bismuth neodecanoate and 124 g of 1,6-hexamethylene diisocyanate are added to the reaction screw. The heating temperatures of the reaction screw in each stage are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively. The heating time for each stage is 4 min. After the end, the product is stretched and pelletized underwater to obtain transparent polyurethane hot melt adhesive particles.

[0041] Example 4.

[0042] S1: Under nitrogen protection, 480 g of waste PET sheets, 41 g of 3,6-dithia-1,8-octanediol, 0.32 g of zinc acetate and 0.22 g of dioctadecyl pentaerythritol diphosphite were sequentially added into a reaction kettle, and stirring was started after the temperature rose to 140° C. The reaction was carried out for 1 hour to obtain a first intermediate;

[0043] S2: The first intermediate, 225 g of poly(carbonate-ether) diol (Mn=3300, CU=30.6%), 0.1 g of stannous octoate and 130 g of 1,4-cyclohexane diisocyanate are added to the reaction screw. The heating temperatures of the reaction screw in each stage are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively. The heating time for each stage is 3 min. After the heating, the product is stretched and pelletized underwater to obtain transparent polyurethane hot melt adhesive particles.

[0044] Example 5.

[0045] S1: Under nitrogen protection, 475 g of waste PET sheets, 42.5 g of 1,4-dithio-2,5-diol, 0.33 g of zinc phosphate and 0.18 g of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] were sequentially added into a reaction kettle, and stirring was started after the temperature rose to 145° C. The reaction was carried out for 2 h to obtain a first intermediate;

[0046] S2: The first intermediate, 206g of poly(carbonate-ether) diol (Mn=3500, CU=54.8%), 0.07g of dibutyltin dilaurate and 128g of tetramethyl meta-xylylene diisocyanate are added to the reaction screw. The heating temperatures of the reaction screw in each stage are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively. The heating time for each stage is 4min. After the end, the product is stretched and pelletized underwater to obtain transparent polyurethane hot melt adhesive particles.

[0047] Example 6.

[0048] S1: Under nitrogen protection, 485 g of waste PET sheets, 45 g of 1,4-dithio-2,5-diol, 0.42 g of manganese acetate and 0.28 g of N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine were sequentially added into a reaction kettle, and stirring was started after the temperature rose to 165°C. The reaction was carried out for 1.5 hours to obtain a first intermediate;

[0049] S2: The first intermediate, 215g of poly(carbonate-ether) diol (Mn=5800, CU=35.2%), 0.08g of bismuth neodecanoate and 135g of 1,4-cyclohexanedimethyl diisocyanate are added to the reaction screw. The heating temperatures of the reaction screw in each stage are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively. The heating time for each stage is 5min. After the end, the product is stretched and pelletized underwater to obtain transparent polyurethane hot melt adhesive particles.

[0050] Comparative Example 1.

[0051] 450g of poly(carbonate-ether) diol (Mn=3300, CU=30.6%), 0.05g of dibutyltin dilaurate and 115g of isophorone diisocyanate were added to the reaction screw. The heating temperatures of the reaction screw at each stage were 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C, respectively. The heating time of each stage was 3min. After the heating was completed, the product was stretched and pelletized underwater to obtain hot melt adhesive particles. Figure 3 This is a photo of the hot melt adhesive particles prepared in this comparative example. It can be seen from the figure that the transparency of the hot melt adhesive particles is low.

[0052] Comparative Example 2.

[0053] 630g of polypropylene glycol (Mn=2000), 0.05g of dibutyltin dilaurate and 115g of isophorone diisocyanate were added to the reaction screw. The heating temperatures of each stage of the reaction screw were 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively. The heating time of each stage was 3min. After the heating, the product was stretched and pelletized underwater to obtain hot melt adhesive particles.

[0054] Comparative Example 3.

[0055] 630g of polybutylene adipate (Mn=2000), 0.05g of dibutyltin dilaurate and 115g of isophorone diisocyanate were added to the reaction screw. The heating temperatures of each stage of the reaction screw were 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively. The heating time of each stage was 3min. After the heating, the product was stretched and pelletized underwater to obtain hot melt adhesive particles.

[0056] Bonding process:

[0057] After the hot melt adhesive pellets are pressed into a film on a flat vulcanizer, they are placed between two pieces of glass and laminated together according to "3mm glass / 2mm hot melt adhesive / 3mm glass". Then they are moved into a vacuum oven and the vacuum degree inside the vacuum oven is maintained above 0.09MPa. The oven temperature is set to rise evenly from 25℃ to 150℃, and then cooled to 40℃ after keeping the temperature for 40 minutes. The sample is taken out to obtain a laminated sample for testing the bonding performance.

[0058] The following table shows the performance parameters of the hot melt adhesive prepared in Examples 1-6 and Comparative Examples 1-3. Among them, the Shore A hardness of the hot melt adhesive is tested according to the standard GB / T531-1999; the tensile strength and elongation at break are tested according to the standards GB / T528-1998 and GB / T528-1982, respectively, with the test temperature of 25°C, the test humidity of 55%, and the tensile machine loading speed of 100mm / min; the bonding strength after bonding the substrate is tested according to the standard GB / T2790-1995; the light transmittance and haze are tested according to the standard GB / T2410-1980, with the test temperature of 25°C and the test humidity of 50%.

[0059]

[0060]

[0061] As can be seen from the results in Table 1, the transparent polyurethane hot melt adhesive prepared in Examples 1-6 exhibits high transparency and low haze, and its light transmittance is as high as 93.5-98.3%, which is 50.8-74.3% higher than similar products; the haze is 0.15-0.26%, which is 1.7-4.6% lower than similar products. This is because the used raw material waste PET sheet itself has excellent transparency, and the amorphous structure of poly (carbonate-ether) diol can maintain its good transparency by reducing the light scattering caused by crystallization. The use of the two effectively enhances the transparency of the polyurethane hot melt adhesive. At the same time, heteroatom sulfur is introduced into the transparent polyurethane hot melt adhesive to enhance the regulation of heteroatom sulfur on the dual soft segment structure of waste PET sheet and poly (carbonate-ether) diol and optimize the compatibility between the two, thereby reducing the haze and light scattering of the material and enhancing the transparency. At the same time, the transparent polyurethane hot melt adhesive has strong adhesion to the glass, with a peel strength of 3.2 to 4.7 N / mm, which is 0.5 to 2.4 N / mm higher than similar products. This is due to the presence of carbonate groups with high cohesive energy in the poly(carbonate-ether) diol structure, and the synergistic effect of the carbonate and ether structures in the structure, which enhances the tensile strength, elongation at break and adhesion to the glass of the transparent polyurethane hot melt adhesive.

[0062] Compared with Examples 1-6, the transmittance, haze and peel strength of the hot melt adhesive prepared in Comparative Example 1 all showed different degrees of decline, mainly due to the lack of waste PET sheet components, and then the lack of heteroatom sulfur regulation of the soft segment, resulting in a decrease in transparency and haze, but due to the presence of carbonate groups with high cohesive energy in the polyol structure, a certain tensile strength and elongation at break are still maintained, and the synergistic effect between the carbonate and ether structures in the polyol structure exists, so that the hot melt adhesive has a certain adhesion to the glass, even if the peel strength is reduced, it can still be maintained above 2N / mm. Comparative Example 2 uses amorphous polypropylene glycol as a soft segment, and the hot melt adhesive can also maintain a certain transparency and haze, but due to the small cohesive energy of polypropylene glycol, the tensile strength is reduced, and the adhesion with the glass is reduced. Comparative Example 3 uses crystalline polyester polyol as a soft segment, and the transparency and haze of the prepared hot melt adhesive both show a trend of a significant decline, and there is no adhesion to the glass, and it can fall directly off the glass.

[0063] Obviously, the above embodiments are only examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the technical solution. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.

Claims

1. A transparent polyurethane hot melt adhesive, characterized in that: It is formed by reacting the following components in parts by mass: 420-510 parts of waste PET flakes, 35-48 parts of sulfur-containing diols, 0.15-0.30 parts of antioxidants, 0.18-0.47 parts of catalysts I, 180-240 parts of poly(carbonate-ether) diols, 0.05-0.12 parts of catalysts II, and 115-142 parts of diisocyanates; The catalyst I is one or a combination of at least two of tetrabutyl titanate, tetraisopropyl titanate, diethyl zinc, zinc octoate, zinc acetate, manganese acetate, manganese phosphate, zinc phosphate, calcium phosphate, zinc oxide and zinc chloride; The catalyst II is one or a combination of at least two of dibutyltin dilaurate, stannous octoate and bismuth neodecanoate.

2. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that: The sulfur-containing diol is one or a combination of at least two of 3,7-dithia-1,9-nonanediol, 3,5-dithia-1,7-heptanediol, 2,2′-thiodiethanol, 3,6-dithia-1,8-octanediol and 1,4-dithia-2,5-diol.

3. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that: The antioxidant is one or a combination of at least two of triethyl phosphite, pentaerythritol bisphosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, dioctadecylpentaerythritol diphosphite, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol and N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.

4. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that: The diisocyanate is one or a combination of at least two of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,4-cyclohexane diisocyanate, tetramethyl meta-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, 1,4-cyclohexane dimethyl diisocyanate and norbornane diisocyanate.

5. The transparent polyurethane hot melt adhesive according to claim 1, characterized in that: The number average molecular weight Mn of the poly(carbonate-ether) diol is 3300-6000, and the carbonate unit content CU is 30%-36%.

6. A method for preparing a transparent polyurethane hot melt adhesive as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Under nitrogen protection, waste PET sheets, sulfur-containing diol, catalyst I and antioxidant are sequentially put into a reactor for heating treatment, and stirred to react after reaching the temperature to obtain a first intermediate; S2: adding the first intermediate, poly(carbonate-ether) diol, catalyst II and diisocyanate into the reaction screw, setting the heating temperature of each stage of the reaction screw, and after heating, cutting the reactants into strips underwater to obtain transparent polyurethane hot melt adhesive particles.

7. The method for preparing the transparent polyurethane hot melt adhesive according to claim 6, characterized in that: In the S1, the reactor is heated to 120-180°C.

8. The method for preparing the transparent polyurethane hot melt adhesive according to claim 6, characterized in that: The reaction time in S1 is 0.5 to 2.5 hours.

9. The method for preparing the transparent polyurethane hot melt adhesive according to claim 6, characterized in that: The heating temperatures in each stage of S2 are 150°C, 180°C, 180°C, 190°C, 190°C, 180°C and 140°C respectively.

10. The method for preparing the transparent polyurethane hot melt adhesive according to claim 6, characterized in that: The heating temperature retention time in each stage of S2 is 3 to 5 minutes.

Citation Information

Patent Citations

  • Preparation method of poly(carbonic ester-ether) glycol and preparation method of catalyst thereof

    CN102432857B

  • Preparation method of poly(carbonic ester-ether) glycol and preparation method of catalyst thereof

    CN102432857A

  • Carbon dioxide based reaction type polyurethane hot melt adhesive and preparation method thereof

    CN108384500A

  • Preparation and application of sulfur-containing copolyester partially derived from biomass

    CN112300372A

  • Poly(carbonate-ether)-based biodegradable polyester and preparation method thereof

    CN113773478A